Yasmin Induced Pulmonary Embolism: a Case Report - Zhu, Xiangjun; Chen, Yin; Yang, Yuehua; Sun, Zhiming (Journal of Advanced Pharmaceutical Science And Technology, 2021)
We evaluate a case report of Yasmin induced pulmonary embolism in order to provide reference for safety use of oral contraceptives.
Keywords: Yasmin; Oral contraceptive; Pulmonary embolism.